Literature review on the application of Hongshan cultural patterns in cultural and creative products - Lin, Lin; Ibrahim, Nur Hisham; Mohamed Salim, Neesa Ameera (Universiti Teknologi MARA, Perak, 2025)
This paper presents a systematic literature review on the application of Hongshan cultural patterns in cultural and creative product design, addressing the lack of comprehensive research on their integration into modern design practices. Despite the historical and artistic significance of Hongshan culture in Northeast China, its visual patterns have not been extensively studied or effectively utilized in contemporary creative industries. This study aims to bridge this gap by critically examining existing research on Hongshan pottery patterns, exploring their role in cultural inheritance and innovation, and analyzing their potential applications in product design. A structured literature search was conducted using academic databases, including Web of Science, Scopus, CNKI, and Google Scholar. Keywords such as "Hongshan culture," "pottery patterns," "cultural creative design," and "heritage innovation" were used to identify relevant studies. Studies lacking empirical analysis or theoretical contributions were excluded to ensure a focused and high-quality review. The findings of this review provide a theoretical foundation for understanding the aesthetic and symbolic characteristics of Hongshan pottery patterns and their application in various cultural and creative products, including daily necessities, stationery, and clothing. Additionally, this study identifies key challenges and opportunities in integrating traditional cultural elements into modern design, offering valuable insights for both researchers and designers. By summarizing existing research and highlighting future directions, this review contributes to a deeper understanding of the intersection between traditional cultural heritage and contemporary creative industries.